Pengembangan UMKM Dalam Pemanfaatan Pemasaran Digital, Design Kemasan Dan Sistem Pencatatan Keuangan Sederhana Pada Toko Kue & Catering Lestari Di Kelurahan Gunung Samarinda Baru - Septian Sampoerna Widodo; Putri Juwita; Nikita Aziz; Ajeng Ayu Putri Lestari (Politeknik Kampar, 2023)
Innovation Development (PI) is a program that provides concrete evidence of the application of knowledge that has been obtained during the study period in the Management and Accounting Study Program. LPPM (Community Service Research Institute) is a forum that accommodates all community service activities for students and lecturers by providing the freedom to develop innovative and creative works to support better economic growth in the city of Balikpapan. The aim of this activity is to find out how marketing strategies in the digital era are to expand product market share, find out how to make labels on packaging as a form of business characteristic, and to find out how far MSMEs carry out simple financial reports for income and expenses. The implementation method for Innovation Development that will be carried out is in stages arranged systematically. The result of this activity was that group 10 was able to complete mentoring activities and seminars in the Gunung Samarinda Baru sub-district.